Effect of solution treatment on the microstructure, phase transformation behavior and functional properties of NiTiNb ternary shape memory alloys fabricated via laser powder bed fusion in-situ alloying - Rui Xi; Hao Jiang; Guichuan Li; Zhihui Zhang; Huiliang Wei; Guoqun Zhao; Jan Van Humbeeck; Xiebin Wang (International Journal of Extreme Manufacturing, 2024)
Post-heat treatment is commonly employed to improve the microstructural homogeneity and enhance the mechanical performances of the additively manufactured metallic materials. In this work, a ternary (NiTi) _91 Nb _9 (at.%) shape memory alloy was produced by laser powder bed fusion (L-PBF) using pre-alloyed NiTi and elemental Nb powders. The effect of solution treatment on the microstructure, phase transformation behavior and mechanical/functional performances was investigated. The in-situ alloyed (NiTi) _91 Nb _9 alloy exhibits a submicron cellular-dendritic structure surrounding the supersaturated B2-NiTi matrix. Upon high-temperature (1273 K) solution treatment, Nb-rich precipitates were precipitated from the supersaturated matrix. The fragmentation and spheroidization of the NiTi/Nb eutectics occurred during solution treatment, leading to a morphological transition from mesh-like into rod-like and sphere-like. Coarsening of the β -Nb phases occurred with increasing holding time. The martensite transformation temperature increases after solution treatment, mainly attributed to: ( i ) reduced lattice distortion due to the Nb expulsion from the supersaturated B2-NiTi, and ( ii ) the Ti expulsion from the β -Nb phases that lowers the ratio Ni/Ti in the B2-NiTi matrix, which resulted from the microstructure changes from non-equilibrium to equilibrium state. The thermal hysteresis of the solutionized alloys is around 145 K after 20% pre-deformation, which is comparable to the conventional NiTiNb alloys. A short-term solution treatment (i.e. at 1 273 K for 30 min) enhances the ductility and strength of the as-printed specimen, with the increase of fracture stress from (613 ± 19) MPa to (781 ± 20) MPa and the increase of fracture strain from (7.6 ± 0.1)% to (9.5 ± 0.4)%. Both the as-printed and solutionized samples exhibit good tensile shape memory effects with recovery rates >90%. This work suggests that post-process heat treatment is essential to optimize the microstructure and improve the mechanical performances of the L-PBF in-situ alloyed parts.